Changes in lipoprotein particle subclasses, standard lipids, and apolipoproteins after supplementation with n-3 or n-6 PUFAs in abdominal obesity: A randomized double-blind crossover study. Issue 5 (May 2021) - Grytten, Elise; Laupsa-Borge, Johnny; Bohov, Pavol; Bjørndal, Bodil; Strand, Elin; Skorve, Jon; Nordrehaug, Jan Erik; Berge, Rolf K.; Rostrup, Espen; Mellgren, Gunnar; Dankel, Simon N.; Nygård, Ottar K.
Summary: Background & aims: Marine-derived omega-3 (n-3) polyunsaturated fatty acids (PUFAs), mainly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), lower circulating levels of triacylglycerols (TAGs), and the plant-derived omega-6 (n-6) PUFA linoleic acid (LA) may reduce cholesterol levels. Clinical studies on effects of these dietary or supplemental PUFAs on other blood fat fractions are few and have shown conflicting results. This study aimed to determine effects of high-dose supplemental n-3 (EPA + DHA) and n-6 (LA) PUFAs from high-quality oils on circulating lipoprotein subfractions and standard lipids (primary outcomes), as well as apolipoproteins, fatty acids, and glycemic control (secondary outcomes), in females and males with abdominal obesity. Methods: This was a randomized double-blind crossover study with two 7-wk intervention periods separated by a 9-wk washout phase. Females (n = 16) were supplemented with 3 g/d of EPA + DHA (TAG fish oil) or 15 g/d of LA (safflower oil), while males (n = 23) received a dose of 4 g/d of EPA + DHA or 20 g/d of LA. In fasting blood samples, we investigated lipoprotein particle subclasses by nuclear magnetic resonance spectroscopy, as well as standard lipids, apolipoproteins, fatty acid profiles, and glucose and insulin. Data were analyzed by linear mixed-effects modeling with 'subjects' as the random factor. Results: The difference between interventions in relative change scores was among the lipoprotein subfractions significant for total very-low-density lipoproteins (VLDLs) (n-3 vs. n-6: −38%∗ vs. +16%, p < 0.001; ∗: significant within-treatment change score), large VLDLs (−58%∗ vs. −0.91%, p < 0.001), small VLDLs (−57%∗ vs. +41%∗, p < 0.001), total low-density lipoproteins (LDLs) (+5.8%∗ vs. −4.3%∗, p = 0.002), large LDLs (+23%∗ vs. −2.1%, p = 0.004), total high-density lipoproteins (HDLs) (−6.0%∗ vs. +3.7%, p < 0.001), large HDLs (+11%∗ vs. −5.3%, p = 0.001), medium HDLs (−24%∗ vs. +6.2%, p = 0.030), and small HDLs (−9.9%∗ vs. +9.6%∗, p = 0.002), and among standard lipids for TAGs (−16%∗ vs. −2.6%, p = 0.014), non-esterified fatty acids (−19%∗ vs. +5.5%, p = 0.033), and total cholesterol (−0.28% vs. −4.4%∗, p = 0.042). A differential response in relative change scores was also found for apolipoprotein (apo)B (+0.40% vs. −6.0%∗, p = 0.008), apoA-II (−6.0%∗ vs. +1.5%, p = 0.001), apoC-II (−11%∗ vs. −1.7%, p = 0.025), and apoE (+3.3% vs. −3.8%, p = 0.028). Conclusions: High-dose supplementation of high-quality oils with n-3 (EPA + DHA) or n-6 (LA) PUFAs was followed by reductions in primarily TAG- or cholesterol-related markers, respectively. The responses after both interventions point to changes in the lipoprotein–lipid–apolipoprotein profile that have been associated with reduced cardiometabolic risk, also among people with TAG or LDL-C levels within the normal range. Registration: Registered under ClinicalTrials.gov Identifier: NCT02647333. Clinical trial registration: Registered at https://clinicaltrials.gov/ct2/show/NCT02647333 .